RELATIVE AGE EFFECT AND CONSTITUENT YEAR EFFECT: AN ANALYSIS OF THE INTERNATIONAL TENNIS FEDERATION RANKING - João Paulo Abreu Moreira; Mariana Calábria Lopes; Larissa Oliveira Faria; Maicon Rodrigues Albuquerque (Journal of Physical Education)
ABSTRACT Relative Age Effect (RAE) and Constituent Year Effect (CYE) seem to influence the process of training young tennis players. The aim of this study was to investigate the presence of these effects in the ranking of junior tennis players of the International Tennis Federation (ITF) and its influence on the score obtained by such tennis players. The results show the presence of the RAE and the CYE (p ≤ 0.05). The regression model identified that the variables "year" and "month" of birth predict the scores of athletes in the ITF ranking with an explained variance of 19%. In conclusion, the ranking composed of various age groups does not seem to be a classification strategy sensitive enough to prevent the RAE and the CYE among junior tennis players.